Pendampingan Guru SD Islam Assa’adah Dalam Penggunaan Media Conference Sebagai Sarana Media Pembelajaran Jarak Jauh - Dimas Kurnia Robby; Lari Andres Sanjaya; Evitha Soraya; Akbar Maulana; Fazzar Malik Ibrahim; Muhammad Revan Marshandi (Jurnal Pengabdian Pada Masyarakat, 2022)
ASSISTANCE FOR ASSA’ADAH ISLAMIC ELEMENTARY SCHOOL TEACHERS IN USING MEDIA CONFERENCES AS DISTANCE LEARNING MEDIA FACILITIES. The development of features in the media conference and various types of media conferences available further adds to the problems in the implementation of distance learning, especially in teachers who experience stuttering technology becomes its own problem in the implementation of distance learning in Assa’adah Islamic Elementary School of Jakarta. This we realize to be the basis of devotion to conduct training in optimizing various media conferences as a means of online learning to teachers with the target of participants able to master several media conferences (Zoom, google meet, Teams) that we teach as a solution to problems that exist in learning.